If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 5(x + -9) = 0 Reorder the terms: 4x + 5(-9 + x) = 0 4x + (-9 * 5 + x * 5) = 0 4x + (-45 + 5x) = 0 Reorder the terms: -45 + 4x + 5x = 0 Combine like terms: 4x + 5x = 9x -45 + 9x = 0 Solving -45 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + 9x = 0 + 45 Combine like terms: -45 + 45 = 0 0 + 9x = 0 + 45 9x = 0 + 45 Combine like terms: 0 + 45 = 45 9x = 45 Divide each side by '9'. x = 5 Simplifying x = 5
| 13t-11=6+4 | | 6x+12=108-6x | | x+14=8(x+7) | | x+14=8(x+6) | | 0.5x^2-x-0.25=0 | | -30n=-27n-12 | | 2y^2-3y=-4 | | 2y^2-3y=4 | | 4a+10=8a+5 | | 0.5x-3+x=15 | | ln(x-1)+ln(x+5)=0 | | 6x^2=4-5x | | 5x+17=x-11 | | 3(h-6)=2(5-2h) | | 8x-12=4x | | 7y-3=4y+9 | | 2(x-1)=3x-1-x | | 4x+80=2x-20 | | 6.4T=64 | | (x^4)-(45*x^3)+(560*x^2)-(1380*x)+864=0 | | t^2=18 | | 7(3x+5)= | | 12X+78+8=13X+14 | | 4(4-4x)+1=2(x+2)-5x | | 4(p+3)=3-2-p | | 10m+11=4(2m+1)+3m | | 5y+11=5y+10 | | -x^2-2x+3=0 | | x^5+3x^4-5x^3+2x^2-7x+3=0 | | -7=-8Y+9 | | 6(2a+5)=-3a-45 | | 2(-1-3x)=-74 |